طبيعة ومجتمع حضارة الموجة الثالثة - عزيز, ريسان; محمد علي حميد, سعد (Journal of College of Education, 2020)
If the discovery of man agriculture represents a major economic revolution in the history of humankind and it has changed the nature of human civilization, the subsequent changes until the industrial revolution in the mid-eighteenth century, became minor and marginal about ten thousand years. However, nearly three hundred years ago, a massive explosion sent shockwaves at a tremendous acceleration along the earth, demolishing the civilized systems of ancient societies and creating an entirely new civilization, of course, the wave of the industrial civilization revolution. Tofler comments: &quot ; The second wave began almost three centuries and is characterized by the mechanism and the intensive production and consumption. It is a new form of factory - based life that has replaced old agriculture on almost a quarter of the globe. This development in the plant is called the second wave of change. " . The Industrial Revolution was more than just machines and factories, but arich social system, multifaceted, contrary to every manifestation of human life, and fought every phenomenon of the first wave, The Industrial Revolution was not a single act, but a complex societal process, in which many tributaries of scientific ability relied on experience and experience, a religious revolution that largely liberated civil society from the control of the Church, and an enlightenment revolution demanding freedom of thought and the individual from the limitations of feudalism and the prevalence of traditions. Led by intellectuals, universities and research centers. A social revolution associated with the emergence of mobile cities, and a technological revolution was the discovery of the steam machine with harnessing the power of steam and then electricity and oil, and the sun as a source of energy instead of animal or wind. Industry - not agriculture - has become the most dynamic and attractive economic activity.